CAD/CAM system influence marginal fit of different ceramic types? - Isabella Gargantini de Almeida; Deborah Bordinassi Antunes; Nathassya Xavier Braun; Andressa Restani; Fabiana Gouveia Straioto; Graziela Avila Galhano (Wolters Kluwer Medknow Publications, 2019)
Objective: This study aimed to evaluate the marginal fit of zirconia and lithium disilicate ceramic restorations processed by computer-aided design (CAD)/computer-aided manufacturing (CAM) system. Materials and Methods: Ten models were prepared from a metal die, on which scanning was carried out to obtain the virtual model for the processing of zirconia and lithium disilicate ceramics using the CAD/CAM technique. Gypsum models were fabricated and used for scanning the restorations. The infrastructures were designed using software, and CAD/CAM was used to fabricate the restorations (n = 10). The analysis of the marginal discrepancy was measured at 12 points of the margin using the original metallic die. For each crown, an arithmetic average of the discrepancy values was obtained. Results: The marginal fit of the copings of lithium disilicate was 133.10 ± 26.87 μm and zirconia was 127.34 ± 47.97 μm. There was no statistically significant difference (P = 0.7709) between the materials. Conclusion: The marginal fit is similar between lithium disilicate and zirconia ceramics milled in the CAD/CAM system used.